Peran Filsafat Pendidikan Islam dalam Kerangka Pendidikan Islam - Mustadi Mustadi; Qomaruddin Qomaruddin (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2023)
In analyzing an issue, Islamic philosophy of education consistently emerges to provide insights into education and the Islamic process, with the aim and objective of achieving an ideal condition. In reality, Islamic philosophy of education moves in two directions: firstly, towards the expansion of philosophical concepts in Islamic education that automatically generates new theories in the education of Islamic sciences, and secondly, towards improvement and innovation in the practices of implementing Islamic education. This research takes the form of a literature review. The primary data used by the researcher includes journals and books on Islamic Philosophy of Education and Islamic Education. The researcher employs the Content Analysis technique by recording factual information and providing detailed and accurate descriptions of various dimensions related to all aspects under investigation. The results of this research indicate that the philosophy of education, especially in the Islamic context, is not only analytical but also provides direction, norms, criticism, and theoretical foundations for educational practices. Islamic philosophy of education, in particular, plays a crucial role in directing education in accordance with the values of the Qur'an and Sunnah.